(Na, K)NbO3–(Bi, Na)TiO3 piezoelectric ceramics for energy-harvesting applications. Issue 14 (November 2015) - Kim, Jinhwan; Koh, Jung-Hyuk
Abstract: A wide variety of energy harvesting materials have been investigated for renewable energy applications. Piezoelectric energy harvesters have attracted attention because of their versatility and reliability. In this work, we prepared (1 − x )(Na0.5 K0.5 )NbO3 – x (Bi0.5 Na0.5 )TiO3 piezoelectric ceramics through conventional mixed oxide fabrication methods with different amounts of (Bi0.5 Na0.5 )TiO3 and various sintering temperatures. We then analyzed the electrical and structural properties of the resulting materials in an attempt to determine the optimal fabrication conditions for enhanced piezoelectric properties. The crystalline properties and surface morphology of (1 − x )(Na0.5 K0.5 )NbO3 – x (Bi0.5 Na0.5 )TiO3 lead-free piezoelectric ceramics were examined via X-ray diffraction and field emission scanning electron microscopy, respectively. We systematically investigated the effect of the sintering temperature on the microstructure, piezoelectric properties, and ferroelectric properties of the materials. The output voltage generated by the (1 − x )(Na0.5 K0.5 )NbO3 – x (Bi0.5 Na0.5 )TiO3 ceramics was measured by a mechanical force system. Optimizing the sintering temperature improved the piezoelectric and ferroelectric properties of (1 − x )(Na0.5 K0.5 )NbO3 – x (Bi0.5 Na0.5 )TiO3 ceramics, increasing their viability for use in energy-harvesting applications.